Sparing or Sharing? Differential Management of Cultivated Land Based on the “Landscape Differentiation–Function Matching” Analytical Framework - Guanyu Ding; Huafu Zhao (Land, 2025)
The sole function of cultivated land of agricultural production is insufficient to meet the diverse demands of modern agriculture. To address land-use conflicts and achieve the United Nations Sustainable Development Goals (SDGs) of zero hunger and reduced carbon emissions by 2030, this study introduces the theory of land sparing and sharing, uses landscape indices to identify spatially fragmented areas, employs a four-quadrant model to assess the matching status of functional supply and demand, and applies correlation analysis to determine the trade-off/synergy relationships between functions. The results indicate the following: (1) Zhengzhou’s farmland landscape exhibits characteristics of low density, low continuity, and high aggregation, with separation zones and sharing zones accounting for 77% and 23% of the total farmland area, respectively. (2) The multifunctional supply (high in the northeast, low in the southwest) and demand (high in the west, low in the east) of farmland show significant mismatches, with PF and EF exhibiting the most pronounced supply–demand mismatches. The “LS-LD and HS-LD” types of farmland account for the largest proportions, at 39% and 35%, respectively. (3) The study area is divided into four primary types: “PCZ, RLZ, BDZ, and MAZ” to optimize supply–demand relationships and utilization patterns. This study enriches the application of land sparing and sharing in related fields, providing important references for policymakers in optimizing land-use allocation and balancing food and ecological security.